2021
DOI: 10.3390/fluids6110416
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility Analysis for Eyring–Powell Nanoliquid Flow Past Magnetized Riga Device with Nonlinear Thermal Radiation

Abstract: The report contained in this article is based on entropy generation for a reactive Eyring–Powell nanoliquid transfer past a porous vertical Riga device. In the developed model, the impacts of viscous dissipation, thermophoresis alongside nonlinear heat radiation and varying heat conductivity are modelled into the heat equation. The dimensionless transport equations are analytically tackled via Homotopy analysis method while the computational values of chosen parameters are compared with the Galerkin weighted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The comparison was done with relevant previous related studies in order to confirm the consistency and exactness of the present computed results. Table 1 denotes the compared results for heat gradient with the work of Tawade et al [4], Ishaq et al [11] and Salawu and Ogunseye [29]. Also, table 2 represents the skin friction numerical results as compared with the previous study of Hayat et al [10] and Ogunseye et al [30].…”
Section: Resultsmentioning
confidence: 97%
“…The comparison was done with relevant previous related studies in order to confirm the consistency and exactness of the present computed results. Table 1 denotes the compared results for heat gradient with the work of Tawade et al [4], Ishaq et al [11] and Salawu and Ogunseye [29]. Also, table 2 represents the skin friction numerical results as compared with the previous study of Hayat et al [10] and Ogunseye et al [30].…”
Section: Resultsmentioning
confidence: 97%
“…Ayub et al [16] utilised slip dynamics to drive EMHD nanofluid movement over a horizontal Riga plate. The irreversible assessment for Eyring-Powell nanofluid flowing via magneto Riga platter with nonlinear thermal radioactive fluxing was studied by Ephesus et al [17]. Rasool and Zhang [18] explored the chemically reactive properties and convection boundary constraints in Powell-Eyring nanomaterial flowing with a radioactive Riga platter.…”
Section: Introductionmentioning
confidence: 99%
“…Fatunmbi et al [43] presented power series homotopy and Galerkin weighted residual method solutions for entropy generation in reactive non-Newtonian dissipative nanofluid MHD flow from a permeable vertical Riga surface embedded in a porous medium with radiative, thermophoresis and variable thermal conductivity effects. They showed that temperature and thermal boundary layer thickness are elevated with thermophoretic parameter whereas the flow is accelerated with increasing magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%